Tulasi (Ocimum sanctum) - Enriched Honey: A Synergistic Blend for Immunity and Wellness - Kumar Patel, Amit; Chaturvedi, Mayank; Nisha, R.; Verma, Anjali; Shanker, Prem; Kumar, Narendra; Singh, Rathodlal; Kumar, Vishal; Ashraf, Nawid (Journal of Neonatal Surgery, 2025)
With growing interest in natural, healthy, and flavourful foods, this study looked into creating a new functional honey product by adding Tulsi (Ocimum sanctum), a well-known medicinal herb. The main goal was to see how adding Tulsi affects the taste, physical qualities, antioxidant strength, and antibacterial effects of honey. The taste test showed that Tulsi gave the honey an herbal, earthy flavor with a slightly bitter and more astringent taste. At the same time, it made the honey less sweet and reduced the usual floral and fruity notes, which led to lower overall liking from tasters. These changes suggest that while Tulsi adds health value, the taste might need adjusting to appeal to more people. When looking at physical properties, the Tulsi-infused honey became darker and had higher moisture, water activity, electrical conductivity, pH, and reducing sugar content. However, its total sugar content dropped. These changes reflect how Tulsi affects the natural makeup of honey. One of the biggest benefits was the boost in antioxidant activity. Tulsi is rich in natural compounds like phenolics and essential oils (such as eugenol), which significantly increased the honey’s ability to fight harmful free radicals. This was confirmed through several tests measuring antioxidant activity. In terms of antibacterial effects, Tulsi honey showed better results against Enterococcus faecalis, meaning it was more effective at stopping this bacteria’s growth. However, it didn’t show much improvement against Pseudomonas aeruginosa. Overall, adding Tulsi made the honey healthier and more medicinal, thanks to its improved antioxidant and antibacterial properties. But it also changed the taste in ways that may not appeal to everyone. So, fine-tuning the recipe will be important to strike the right balance between